2014
DOI: 10.1590/s0044-59672014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic parameters and growth in seedlings of Bertholletia excelsa and Carapa guianensis in response to pre-acclimation to full sunlight and mild water stress

Abstract: Light and water are important factors that may limit the growth and development of higher plants. The aim of this study was to evaluate photosynthetic parameters and growth in seedlings of Bertholletia excelsa and Carapa guianensis in response to pre-acclimation to full sunlight and mild water stress. I used six independent pre-acclimation treatments (0, 90 (11h15-12h45), 180 (10h30-13h30), 360 (09h00-15h00), 540 (07h30-16h30) and 720 min (06h00-18h00)) varying the time of exposure to full sunlight (PFS) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
4
0
6
Order By: Relevance
“…According to Azevedo (2014), when subjected to shading conditions, plants tend to increase chlorophyll a, b and total indexes in order to maximize light capture, a fact not found in the present work. In this sense, Lenhard et al (2013) stated that the increase of photosynthetic pigments in plants conducted under low light intensity is an alternative to optimize photophosphorylation and induce higher energy production and thus maximize their photosynthetic process.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…According to Azevedo (2014), when subjected to shading conditions, plants tend to increase chlorophyll a, b and total indexes in order to maximize light capture, a fact not found in the present work. In this sense, Lenhard et al (2013) stated that the increase of photosynthetic pigments in plants conducted under low light intensity is an alternative to optimize photophosphorylation and induce higher energy production and thus maximize their photosynthetic process.…”
Section: Resultsmentioning
confidence: 46%
“…De acordo com Azevedo (2014), ao serem submetidas a condições de sombreamento, as plantas tendem a aumentar os índices de clorofila a, b e total com o objetivo de maximizar a captura de luz, fato não constatado no presente trabalho. Nesse sentido, Lenhard et al (2013) afirmaram que o aumento dos pigmentos fotossintéticos em plantas conduzidas sob baixa intensidade luminosa é uma alternativa para otimizar a fotofosforilação e induzir a maior produção de energia e, assim, maximizar seu processo fotossintético.…”
Section: Resultsunclassified
“…Incremento médio em altura (H), incremento médio em diâmetro do colo (D), número de folhas (NF), área foliar (AF) e área foliar específica (AFE) de mudas de Aniba parviflora aos 300 dias, em Santarém, PA. A AFE aumentou significativamente em função do aumento dos níveis de sombreamento (Tabela 2). O mesmo resultado foi encontrado para Handroanthus heptaphyllus (Borges et al, 2014), Swietenia macrophylla (Gonçalves et al, 2012;Azevedo & Marenco, 2012), Minquartia guianensis (Azevedo & Marenco, 2012), Bertholletia excelsa e Carapa guianensis (Azevedo, 2014), indicando que durante o desenvolvimento da planta o regime de luz pode afetar a estrutura foliar e partição de assimilados, sendo que as plantas cultivadas em baixa intensidade de luz muitas vezes têm folhas mais finas e maiores. Geralmente, estas alterações têm por objetivo aumentar a captação da luz incidente, aumentando a eficiência fotossintética da planta (Lambers et al, 1998).…”
Section: Resultsunclassified
“…Valores semelhantes foram encontrados por Souza et al (2011), Lenhard et al (2013) e Azevedo (2014), mostrando que a exposição prolongada das plantas à luz povocou a redução dos pigmentos fotossintéticos, como também pode ter induzido a fotoxidação. Plantas em condição de sombreamento tendem a aumentar a concentração de clorofila, para a maximização da captura de luz (Azevedo, 2014), com o aumento na proporção de clorofila b em relação à a (Critchley, 1999). Folhas cultivadas sob baixas intensidades de luz apresentam maiores teores de clorofila por unidade de peso, e folhas de sombra apresentam maior concentração de clorofila, quando comparadas às de sol.…”
Section: Resultsunclassified
“…Several studies showed that variations in chlorophyll content are related to plant photosynthetic capacity, development stage and environmental stresses (Kitajima & Hogan 2003, Ishida et al 2005, Mielke et al 2010, Grossnickle 2012, Campoe et al 2014, Costa-Azevedo 2014. Therefore, chlorophyll content is an important indicator of photosynthetic efficiency, carbon uptake, and fitness of plants and ecosystems (Pettorelli et al 2005, Grace et al 2007.…”
Section: Introductionmentioning
confidence: 99%